Analysis of State-of-the-Art Converter Topologies for Interfacing of Hydrogen Buffer with Renewable Energy Systems - Andrijanovitsh, Anna; Steiks, Ingars; Zakis, Janis; Vinnikov, Dmitri (Electrical, Control and Communication Engineering, 2011)
This paper compares state-of-the-art DC/DC converter topologies for electrolyzer and fuel cell applications in renewable energy systems (RES). The main components of the hydrogen-based energy storage system should be connected to the DC-bus of a RES via separate interface converters: the electrolyzer is interfaced by the step-down DC/DC converter, while the fuel cell is connected through the step-up DC/DC converter. Because of the high input and output voltage differences the topologies with a high-frequency voltage matching transformer are analyzed. The inverter and rectifier sides of the discussed DC/DC converters presented in schemes are analyzed in detail.